Africa in Global Politics in the Twenty-First Century: A Pan-African Perspective - Olayiwola Abegunrin (PALGRAVE macmillan, 2009)
In the twenty-first century, Africa has become an important source of US energy imports and the world's natural resources. It has also become the epicentre of the world's deadly health epidemic, HIV/AIDS, and one of the battlegrounds in the fight against terrorism. Africa is now a major player in global affairs.